The adventures of Pinocchio : tale of a puppet - Collodi, Carlo, 1826-1890 (Lothrop, Lee & Shepard Books, 1983)
Pinocchio, a wooden puppet full of tricks and mischief, with a talent for getting into and out of trouble, wants more than anything else to become a real boy.